Latitudinal difference in the molecular distributions of lipid compounds in the forest atmosphere in China. (1st February 2022) - Zhang, Donghuan; Ren, Hong; Hu, Wei; Wu, Libin; Ren, Lujie; Deng, Junjun; Zhang, Qiang; Sun, Yele; Wang, Zifa; Kawamura, Kimitaka; Fu, Pingqing
Abstract: Lipids are important biogenic markers to indicate the sources and chemical process of aerosol particles in the atmosphere. To better understand the influences of biogenic and anthropogenic sources on forest aerosols, total suspended particles (TSP) were collected at Mt. Changbai, Shennongjia, and Xishuangbanna that are located at different climatic zones in northeastern, central and southwestern China. n- Alkanes, fatty acids and n- alcohols were detected in the forest aerosols based on gas chromatography-mass spectrometry. The total concentrations of aliphatic compounds ranged from 15.3 ng m −3 to 566 ng m −3, and fatty acids were the most abundant (44–95%) followed by n- alkanes and n- alcohols. Low molecular weight- (LFAs) and unsaturated fatty acids (UnFAs) showed diurnal variation with higher concentrations during the nighttime in summer, indicating the potential impact from microbial activities on forest aerosols. The differences of oleic acid (C18:1 ) and linoleic acid (C18:2 ) concentrations between daytime and nighttime increased at lower latitude, indicating more intense photochemical degradation occurred at lower latitude regions. High levels of n- alkanes during daytime in summer with higher values of carbon preference indexes, combining the strong odd carbon number predominance with a maximum at C27 or C29, implied the high contributions of biogenic sources, e.g., higher plant waxes. In contrast, higher concentrations of low molecular weight n- alkanes were detected in winter forest aerosols. Levoglucosan showed a positive correlation (R 2  > 0.57) with high- and low molecular weight aliphatic compounds in Mt. Changbai, but such a correlation was not observed in Shennongjia and Xishuangbanna. These results suggest the significant influence of biomass burning in Mt. Changbai, and fossil fuel combustion might be another important anthropogenic source of forest aerosols. This study adds useful information to the current understanding of forest organic aerosols at different geographical locations in China. Graphical abstract: Image 1 Highlights: Seasonal differences in impact of biogenic/anthropogenic sources on forest aerosols. The photodegradation of unsaturated fatty acids was more severe in lower latitudes. Both biomass burning and fossil fuel combustion contributed to the Mt. Changbai aerosols. Different patterns of lipids in forest aerosols at different locations in China.